1995
DOI: 10.1016/0092-8674(95)90432-8
|View full text |Cite
|
Sign up to set email alerts
|

The S. pombe cdc15 gene is a key element in the reorganization of F-actin at mitosis

Abstract: The S. pombe cdc15 gene is essential for cell division. cdc15ts mutants do not form a septum, but growth and nuclear division continue, leading to formation of multinucleate cells. The earliest step in septum formation and cytokinesis, rearrangement of actin to the center of the cell, is associated with appearance of hypophosphorylated cdc15p and formation of a cdc15p ring, which colocalizes with actin. Loss of cdc15p function impairs formation of the actin ring. The abundance of cdc15 mRNA varies through the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
318
1
5

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(336 citation statements)
references
References 36 publications
12
318
1
5
Order By: Relevance
“…Taken together, our data favor the model that Cdc15p could promote tER biogenesis at the division site. It has been shown that overexpression of Cdc15p causes actin relocalization to the equatorial region in interphase cells (Fankhauser et al, 1995). To assess whether this is sufficient for the early secretory pathway compartments polarization, we overexpressed Cdc15p under the nmt1 promoter in cells arrested in interphase by the use of cdc25-22 genetic background (Gould and Nurse, 1989).…”
Section: Early Secretory Pathway In Fission Yeastmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, our data favor the model that Cdc15p could promote tER biogenesis at the division site. It has been shown that overexpression of Cdc15p causes actin relocalization to the equatorial region in interphase cells (Fankhauser et al, 1995). To assess whether this is sufficient for the early secretory pathway compartments polarization, we overexpressed Cdc15p under the nmt1 promoter in cells arrested in interphase by the use of cdc25-22 genetic background (Gould and Nurse, 1989).…”
Section: Early Secretory Pathway In Fission Yeastmentioning
confidence: 99%
“…During early mitosis, actin is assembled into a ring structure through the action of several actin nucleating and bundling proteins and molecular motors. These include the formin Cdc12p (Chang et al, 1997), profilin Cdc3p (Balasubramanian et al, 1992), the extended Fer/CIP4 (EFC) domain protein Cdc15p (Fankhauser et al, 1995), and the myosin heavy chain Myo2p (Kitayama et al, 1997) together with its light chains Cdc4p (McCollum et al, 1995;Naqvi et al, 1999) and Rlc1p (Le Goff et al, 2000). It has been proposed that activation of the signaling cascade referred to as the septation initiation network (SIN) triggers actomyosin ring constriction upon nuclear division (for review see Krapp et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the regulation of budding yeast Hof1p appears to be conserved between SIN and MEN. Fission yeast Cdc15p is one of two functional homologues of Hof1p [51][52][53], which is the only established target of budding yeast Mob1p/ Dbf2p in cytokinesis [37]. Furthermore, Cdc15p is phosphorylated on a conserved RXXS motif that can be targeted by Mob1p/Sid2p [53].…”
Section: Septation Initiation Network (Sin) In Schizosaccharomyces Pombementioning
confidence: 99%
“…PSTPIP appears to be the mammalian homologue of the fission yeast Schizosaccharomyces pombe CDC15p, a protein involved in the organization of the cytokinetic cleavage furrow (20). It was reported that PSTPIP associates with cortical actin during most of the cell cycle and translocates at the cleavage furrow during cytokinesis (18).…”
mentioning
confidence: 99%